Row-Column Designs for Two Level Factorial Experiments - Kaushal Kumar Yadav; Sukanta Dash; Baidya Nath Mandal; Rajender Parsad (Journal of the Indian Society of Agricultural Statistics, 2025)
Row-column designs are useful for the experimental situations in which there are two cross classified sources of heterogeneity in the experimental material. Often it is desired to compare two or more factors in row-column set up where only two units can be accommodated in a single column. In this article, a general method of construction has been developed to generate row-column designs for factorial experiments with two rows which permit orthogonal estimation of all main effects and specific two factor interactions as per the choice of experimenters.